Role of Blood Neurofilaments in the Prognosis of Amyotrophic Lateral Sclerosis: A Meta-Analysis - Zhou, Yan-ni; Chen, You-hong; Dong, Si-qi; Yang, Wen-bo; Qian, Ting; Liu, Xiao-ni; Cheng, Qi; Wang, Jiu-cun; Chen, Xiang-jun (Frontiers in Neurology, 2021)
Background Neurofilaments in cerebrospinal fluid (CSF) and in blood are considered promising biomarkers of amyotrophic lateral sclerosis (ALS) because their levels can be significantly increased in patients with ALS. However, the roles of neurofilaments, especially blood neurofilaments, in the prognosis of ALS are inconsistent. We performed a meta-analysis to explore the prognostic roles of blood neurofilaments in ALS patients. Methods We searched all relevant studies on the relationship between blood neurofilament levels and the prognosis of ALS patients in PubMed, Embase, Scopus, and Web of Science before February 2, 2021. The quality of the included articles was assessed using the Quality in Prognosis Studies (QUIPS) scale, and R (version 4.02) was used for statistical analysis. Results Fourteen articles were selected, covering 1619 ALS patients. The results showed that higher blood neurofilament light chain (NfL) levels in ALS patients were associated with a higher risk of death (medium vs low NfL level: HR = 2.43, 95% CI [1.34–4.39], p < 0.01; high vs low NfL level: HR = 4.51, 95% CI [2.45–8.32], p < 0.01). There was a positive correlation between blood phosphorylated neurofilament heavy chain (pNfH) levels and risk of death in ALS patients (HR = 1.87, 95% CI [1.35–2.59], p < 0.01). The levels of NfL and pNfH in blood positively correlated with disease progression rate (DPR) of ALS patients (NfL: summary r = 0.53, 95% CI [0.45–0.60], p < 0.01; pNfH: summary r = 0.51, 95% CI [0.24–0.71], p < 0.01). Conclusion The blood neurofilament levels can predict the prognosis of ALS patients; specifically, higher levels of blood neurofilaments are associated with a greater risk of death.